Diagenesis and Porosity-Reducing Mechanism in Moragot Field, Pattani Basin, Gulf of Thailand - Uphatam, Praiwan (Bulletin of Earth Sciences of Thailand, 2021)
Lower to middle mid-Miocene sandstones are the petroleum reservoirs in Moragot Field, southern part of Pattani Basin, Thailand. These sandstones were deposited in continental, transitional and marine environments. This study combined wireline logs, thin section and scanning electron microscope to enhance the understanding of the diagenesis and porosity-reducing mechanisms in this area. In general, porosity decreases with depth due to increasing overburden. A combination of cementation with a high clay content and poor sorting contributed destroying porosity. In contrast, quartz overgrowths have a positive correlation with porosity. Moreover, except quartz cement, dissolution of framework grains and cement also recovers porosity lost by diagenesis. The reservoir interval of Moragot Field is stratigraphically deeper than other areas plus the depositional environment changes to a transitional clay-rich environment.